2021
DOI: 10.1007/s10230-021-00754-6
|View full text |Cite
|
Sign up to set email alerts
|

Geoenvironmental Study of Gold Mining Tailings in a Circular Economy Context: Santa Barbara, Minas Gerais, Brazil

Abstract: We characterized the tailings from the Santa Barbara tailings dam, which is located in Minas Gerais, southeastern Brazil, to: (i) identify its chemical, mineralogical, and metallurgical properties, and (ii) perform an environmental evaluation of the water at the surface of the tailings facility. The potential recovery of elements such as Sb, As, and Au was also considered for potential tailings reuse. The water was alkaline, with maximum pH values of ≈ 10, and contained potentially toxic elements, such as Sb (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…S6). Such detailed information is essential to assess the metallurgical potential for reuse and the impacts associated with the disposal of these tailings 6,9 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S6). Such detailed information is essential to assess the metallurgical potential for reuse and the impacts associated with the disposal of these tailings 6,9 .…”
Section: Resultsmentioning
confidence: 99%
“…These models aim to add new value to tailings by identifying the proper destination of potentially hazardous materials 12 Studies using a combination of characterization techniques are the starting point to add value and increased knowledge to these wastes 13 . The integration of analytical techniques such as specific chemical analysis for solids, mineralogical and particle size distribution, and density determination, can be found in a number of publications 6,[13][14][15][16][17][18][19] (demonstrating that this characterization stage is critical to evaluating and understanding the waste deposits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pier-Luc Labonté-Raymond et al have studied the impact of climate change on the drainage system of tailings ponds 8 . MG Lemos et al identified the chemical, mineralogical and metallurgical properties of gold tailings located in the Santa Barbara mine 9 . Baker K E et al applied process safety management tools to the tailings storage and transportation system, and visually characterized the possible hazards and control measures to prevent accidents 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Pier-Luc Labonté-Raymond et al have studied the impact of climate change on the drainage system of tailings ponds [8] . MG Lemos et al identi ed the chemical, mineralogical and metallurgical properties of gold tailings located in the Santa Barbara mine [9] . Baker K E et al applied process safety management tools to the tailings storage and transportation system and visually characterized the possible hazards and control measures to prevent accidents [10] .…”
Section: Introductionmentioning
confidence: 99%